(untitled) (International Journal of Social Research & Innovation, 2021)
The under-representation of women in Information Technology (IT) sector in the Maldives reflects in the overall under-representation of women in Science, Technology, Engineering and Mathematics (STEM) and in paid employment in general. Despite the challenges, a significant number of Maldivian women complete higher education in IT, but very few succeed to make a life-long career in IT. Hence, the purpose of the research presented in this paper was to analyze the societal barriers that impact Maldivian women pursuing IT-related careers. The findings of this correlational study revealed that antiquated thinking, gender discrimination, and marital status were perceived to have a higher significant negative impact on Maldivian women pursuing IT-related careers, while work-home conflict or the double burden of domestic work and work demands, and age discrimination had a lesser perceived correlation. The findings have implications for policy on promoting gender equality in the workforce in the Maldives.